Education as the Key to Escaping Poverty in Middle-Income Countries - Pratysto, Tangguh (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This research aims to examine and prove the determinant variables that can reduce poverty problems in middle-income countries in the long term. The main reason poverty problems are essential to solve is that the poor should be cared for by the state. After all, every citizen has the right to work and a decent standard of living. This research method is quantitative, conducted using generalized least squares regression in 54 middle-income countries from 1999 to 2022, and supported by classical assumption diagnostic tests. The study's main findings prove that tertiary education can reduce the poverty gap. Increasing income per capita, expanding the coverage of social insurance program policies, and reducing the rural population can also reduce the poverty gap. The implications of these findings for policymakers should support tertiary education to reduce poverty in the long term.